Leaf gas exchange and ﬂuorescence of Phillyrea latifolia, Pistacia lentiscus and Quercus ilex saplings in severe drought and high temperature conditions - Filella, I; Llusia, J; Piñol, J; Penuelas, J (Environmental and Experimental Botany, 1998)
Saplings of Phillyrea latifolia, Pistacia lentiscus and Quercus ilex were witheld watering for 7 days, followed by reirrigation. Incident photosynthetic photon ﬂux density (PPFD), leaf temperature, net photosynthetic rates, stomatal conductance, and photochemical efﬁciency of the photosystem II (DF:F’m) were measured three times during the day. The watered plants had higher photosynthetic rates, stomatal conductances, DF:F’m and ETR than non-watered plants. However, watered plants were mildly water stressed as shown by low ratio of variable to maximal ﬂuorescence (Fv:Fm) and high non-photochemical ﬂuorescence quenching (qN). Their DF:F%m was low in the morning and increased in the evening, following the variations in PPFD. Watered plants of Q. ilex had lower photosynthetic activity, stomatal conductance and photosynthetic radiation use efﬁciency than Ph. latifolia and P. lentiscus, and, conversely, reached the highest DF:F%m and ETR. This seems to indicate a different relationship between photosynthetic activity and electron transport rate in Q. ilex compared to the other two species. Ph. latifolia and P. lentiscus appeared to be better adapted to severe drought than Q. ilex.
Keywords: Drought; hF/F’m; phillyrea latifolia; photosynthetic rate; Pistacia lentiscus; Quercus ilex; Stomatal conductance